A hipóstase Noûs em Plotino: o itinerário teórico e o debate acerca do problema da identidade do Intelecto com as Ideias na Enéada V.3 [49] - Silva, Robert Brenner Barreto da (2019)
The question of the identity between Intellect and Ideas in Plotinus emerges from an epistemological problem related to the possession of true knowledge in the perspective of a cognoscitive relation in which there is not a solid base. In order to guarantee the ontoepistemological enterprise, Plotinus recurs to the parmenedian union between being and thinking in the hypostasis stance, with the aim to affirm at the same time the identity and the distinction between Intellect and Ideas, which allows to maintain the relationship between the one who knows and that which is known, necessary to the process of knowledge. These concepts are connected into the conception of self-knowledge, which requires both that the Intellect has as his primary activity the pure thinking and that the content of his thought must be intern to himself, that is to say, the intelligible must be intern to Intellect. The ideas need to be in the Intellect, because any external cognition is, according to Plotinus understanding, relative to mere representations and not about the things as they are in themselves. The internality of Ideas in Intellect, therefore, offers the basis to epistemology. If it is not in this way, it could be possible to suspend the evaluation, what results in a question ad infinitum about the source of knowledge. However, as I will discuss throughout this work, emerges the problem about how to reconcile the following theses: the Intellect is identical to intelligibles and that at the same time they are distinct as they perform a subject and object roles. The formulation of this apparent contradiction can be textually found in Sextus Empiricus when he criticizes the dogmatists - claiming that self-knowledge is impossible. The Nous philosophy of Plotinus, for his turn, seems to respond to this impasse in the light of the philosophical tradition. This work emphasizes Plato and Aristotle as the most important sources. This influence can be summarizing in two concepts: the supreme genres of Sophist and the energeia from Aristotle‘s metaphysics. The last one will be crucial to understand the problem and the solutions, as it will work as a hypothesis of interpretation according to what it will be able to investigate if it is possible to reconcile the two apparent contradictory theses. To achieve the research‘s goal, I will do a distinction not at the level of substance, but at the level of act. So, Intellect and Intelligibles would continue to be identical and distinct in the sense of who acts as the thinker and who acts as the object of thought. To accomplish the aim of analyzing the problematic, as well as to exam the viability of the hypothesis based on the Energeia, it will be made an analysis of the V.3 treatise of Enneads and of other texts, of which V.5 stands out.